PERTARUNGAN IDENTITAS (KELUARGA) SAPI MADURA - Ardhie Raditya (Journal of Urban Sociology, 2020)
So far, studies on the identity of Madurese bulls have not been adequately identified, especially the way of seeing of the Madurese bulls family. Madurese bulls are often seen as a secondary complement to the life of the Madurese. In fact, historically, metaphysically, and politically, Madures bulls are part of the 'close family' of the Madurese, whether we realize it or not. The power of the media industry, which has an impact on the cultural industry, has changed the identity of Madurese bulls as an industrial product. The advertisements for "Marjan" and "Samsung Galaxy" are an actual phenomena of the influence of the cultural industry and media culture because both advertisements show Madurese bulls. The Madurese bulls family in Sapodi (the legendary island as the best Madurese Bulls producer in Madurese bulls race Island) perceives the commercial viewing of “Marjan” Madurese bulls and “Galaxy” Madurese bulls with different seeing among their family members. This reception resulted in a struggle for recognition between them so as to create an unstable meaning of Madureseness identity because the audience of the two commercials represented each other as determining the 'authenticity' of Madurese bulls, although basically the 'authenticity' had been lost by the magic of the mass media.Keywords : Struggle of Identity, Madurese Bulls, and Madurese Bulls Family